The information system for support of the license Earth resources using process; Korus 2001; Vol. 1 - Markov N. G. Nikolai Grigorevich (2001, 2001)
In this paper, an information system, developed in the Laboratory of Geoinformation Systems of the Cybernetic Center of Tomsk Polytechnic University (TPU), which is intended to solve the problems of meeting corporate demands is considered. The created system is intended to be used by official organizations that deal with the licensing of the Earth's natural resources using processes from the local up to the federal levels, and also to be used by the experts of departments that license the companies and users of these resources.